The heart of change field guide : tools and tactics for leading change in your organization - Cohen, Dan S. (Boston, Mass. : Harvard Business School Press, 2005)
"In 1996, John P. Kotter's Leading Change became a runaway best seller, outlining an eight-step program for organizational change that was embraced by executives around the world. Then, Kotter and co-author Dan Cohen's The Heart of Change introduced the revolutionary "see-feel-change" approach, which helped executives understand the crucial role of emotion in successful change efforts. Now, The Heart of Change Field Guide provides leaders and managers tools, frameworks, and advice for bringing these breakthrough change methods to life within their own organizations. Written by Dan Cohen and with a foreword by John P. Kotter, the guide provides a practical framework for implementing each step in the change process, as well as a new three-phase approach to execution: creating a climate for change, engaging and enabling the whole organization, and implementing and sustaining change. Hands-on diagnostics-including a crucial 'change readiness module'-reveal the dynamics that will help or hinder success at each phase of the change process. Both flexible and scaleable, the frameworks presented in this guide can be tailored for any size or type of change initiative. Filled with practical tools, checklists, and expert commentary, this must-have guide translates the most powerful approaches available for creating successful change into concrete, actionable steps for you and your organization. Dan Cohen is the co-author, with John P. Kotter, of The Heart of Change, and a principal with Deloitte Consulting, LLC" -- Publisher description.
Introduction -- Step one: Increase urgency- getting people to say "let's do something" -- Step two: Build guiding teams- finding the right people to make change happen -- Step three: Get the vision right- seeing the future -- Step four: Communicate for buy-in- getting the message right and keeping it right -- Step five: Enable action- breaking the barriers to change -- Step six: Create short-term wins-we all need to see and feel that we are making progress -- Step seven: Don't let up- being persistant is hard work -- Step eight: Make it stick- weaving the new behavior into the fabric of the organization -- The final module: Getting back to go and change readiness.
Includes index.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Organizational change; Changement organisationnel; Management; Reorganisation; Organizational change; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books